Reduced proliferation of endothelial colony-forming cells in unprovoked venous thromboembolic disease as a consequence of endothelial dysfunction. - Rubicel Hernandez-Lopez; Antonieta Chavez-Gonzalez; Patricia Torres-Barrera; Dafne Moreno-Lorenzana; Norma Lopez-DiazGuerrero; David Santiago-German; Irma Isordia-Salas; David Smadja; Mervin C Yoder; Abraham Majluf-Cruz; J Antonio Alvarado-Moreno (PLoS ONE)
Background Venous thromboembolic disease (VTD) is a public health problem. We recently reported that endothelial colony-forming cells (ECFCs) derived from endothelial cells (EC) (ECFC-ECs) from patients with VTD have a dysfunctional state. For this study, we proposed that a dysfunctional status of these cells generates a reduction of its proliferative ability, which is also associated with senescence and reactive oxygen species (ROS). Methods and results Human mononuclear cells (MNCs) were obtained from peripheral blood from 40 healthy human volunteers (controls) and 50 patients with VTD matched by age (20-50 years) and sex to obtain ECFCs. We assayed their proliferative ability with plasma of patients and controls and supernatants of cultures from ECFC-ECs, senescence-associated β-galactosidase (SA-β-gal), ROS, and expression of ephrin-B2/Eph-B4 receptor. Compared with cells from controls, cells from VTD patients showed an 8-fold increase of ECFCs that emerged 1 week earlier, reduced proliferation at long term (39%) and, in passages 4 and 10, a highly senescent rate (30±1.05% vs. 91.3±15.07%, respectively) with an increase of ROS and impaired expression of ephrin-B2/Eph-4 genes. Proliferation potential of cells from VTD patients was reduced in endothelial medium [1.4±0.22 doubling population (DP)], control plasma (1.18±0.31 DP), or plasma from VTD patients (1.65±0.27 DP). Conclusions As compared with controls, ECFC-ECs from individuals with VTD have higher oxidative stress, proliferation stress, cellular senescence, and low proliferative potential. These findings suggest that patients with a history of VTD are ECFC-ECs dysfunctional that could be associated to permanent risk for new thrombotic events.